2020
DOI: 10.11648/j.sjac.20200802.18
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition and Adsorption Properties of <i>Commelina benghalensis</i> Leaves Extract on Mild Steel in 1M H<sub>2</sub>SO<sub>4</sub> Solution

Abstract: The corrosion inhibition of mild steel in 1M sulphuric acid solution by the ethanol extract of Commelina benghalensis (C. B) leaves was determined using gravimetric technique. Phytochemical analysis was carried out on the extract and the effect of extract concentration, temperature, immersion time and acid concentration on the corrosion process was determined. The corrosion inhibition efficiency of the extract increased with increase in the concentration of the extract and decreased with increase in temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…This may be attributed to the protective ability of the leave extract. Similar findings have been reported by Odidika et al [12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may be attributed to the protective ability of the leave extract. Similar findings have been reported by Odidika et al [12].…”
Section: Discussionsupporting
confidence: 93%
“…The results show that the weight loss increased with increase in extract concentration. The more the interaction between the compounds present in the extract the more the protection of the coupons, Odidika et al [12] reported similar observation.…”
Section: Discussionmentioning
confidence: 77%